2003
DOI: 10.1128/jb.185.9.2774-2785.2003
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in the Microcystin Synthetase Operon mcyABC and Impact on Microcystin Production in Microcystis Strains

Abstract: Toxic Microcystis strains often produce several isoforms of the cyclic hepatotoxin microcystin, and more than 65 isoforms are known. This has been attributed to relaxed substrate specificity of the adenylation domain. Our results show that in addition to this, variability is also caused by genetic variation in the microcystin synthetase genes. Genetic characterization of a region of the adenylation domain in module mcyB1 resulted in identification of two groups of genetic variants in closely related Microcysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
222
3
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(243 citation statements)
references
References 53 publications
14
222
3
4
Order By: Relevance
“…For the mcy genes, it has been shown that the operon structure and the order of genes varies between the genera Planktothrix, Anabaena and Microcystis (reviewed by Dittmann & Börner, 2005). In addition, recombination between different domains within the mcy gene clusters, point mutations and deletion of gene regions, as well as lack of substrate specificity of A-domains have been shown to contribute to the synthesis of different microcystin isoforms (Fewer et al, 2008;Mikalsen et al, 2003;Tooming-Klunderud et al, 2008). A deletion within the second module of mcyA and the first module of mcyB resulted in the synthesis of another cyanotoxin, nodularin (Moffitt & Neilan, 2004;Rantala et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For the mcy genes, it has been shown that the operon structure and the order of genes varies between the genera Planktothrix, Anabaena and Microcystis (reviewed by Dittmann & Börner, 2005). In addition, recombination between different domains within the mcy gene clusters, point mutations and deletion of gene regions, as well as lack of substrate specificity of A-domains have been shown to contribute to the synthesis of different microcystin isoforms (Fewer et al, 2008;Mikalsen et al, 2003;Tooming-Klunderud et al, 2008). A deletion within the second module of mcyA and the first module of mcyB resulted in the synthesis of another cyanotoxin, nodularin (Moffitt & Neilan, 2004;Rantala et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other genes of the microcystin encoding gene cluster, e.g. mcyA, mcyB, and mcyT, have been reported in non-MC-producing Microcystis and Planktothrix strains (Mikalsen et al 2003;Kurmayer et al 2004;Christiansen et al 2008). Genes encoding the biosynthesis of other cyanobacterial toxins, e.g.…”
Section: R Curvata From Hartbeespoort Dam Than To Cylindrospermopsismentioning
confidence: 99%
“…Also, the genetic aspect of toxin production i.e. the enzyme responsible for toxin production, enzyme structure and genes involved in toxin production by this cyanobacterial genus has also been investigated by several workers [19][20][21][22]. Studies have revealed that there is significant influence of culture age on microcystin production.…”
Section: Discussionmentioning
confidence: 99%